A state level analyses of suicide and the COVID-19 pandemic in Mexico - Ann John (BMC Psychiatry, 2022)
BackgroundWhile suicide rates in high- and middle-income countries appeared stable in the early stages of the pandemic, we know little about within-country variations. We sought to investigate the impact of COVID-19 on suicide in Mexico’s 32 states and to identify factors that may have contributed to observed variations between states.MethodsInterrupted time-series analysis to model the trend in monthly suicides before COVID-19 (from Jan 1, 2010, to March 31, 2020), comparing the expected number of suicides derived from the model with the observed number for the remainder of the year (April 1 to December 31, 2020) for each of Mexico’s 32 states. Next, we modeled state-level trends using linear regression to study likely contributing factors at ecological level.ResultsSuicide increased slightly across Mexico during the first nine months of the pandemic (RR 1.03; 95%CI 1.01–1.05). Suicides remained stable in 19 states, increase in seven states (RR range: 1.12–2.04) and a decrease in six states (RR range: 0.46–0.88). Suicide RR at the state level was positively associated with population density in 2020 and state level suicide death rate in 2019.ConclusionsThe COVID-19 pandemic had a differential effect on suicide death within the 32 states of Mexico. Higher population density and higher suicide rates in 2019 were associated with increased suicide. As the country struggles to cope with the ongoing pandemic, efforts to improve access to primary care and mental health care services (including suicide crisis intervention services) in these settings should be given priority.